An Educational Experience in the Area of Librarianship: Innovating Through Practical and Creative Teaching Strategies - Chaves Salgado, Lorena (2022)
The article aims to present the process developed to adapt, innovate and improve the teaching strategies applied in the course "Fundamentals of Library and Information Sciences" of the School of Library and Information Sciences of the University of Costa Rica. For this purpose, a diagnosis was made to 56 students enrolled during the I cycle 2019 and based on their needs and ways of learning, 3 didactic strategies that facilitated the acquisition of knowledge, meaningful learning and the acquisition of soft skills were devised and applied. As a result, the activities carried out were widely accepted by the students, which was reflected both in their evaluations and those applied to teachers.